Hubungan Faktor Risiko Usia dan Jenis Kelamin Dengan Kejadian Hipertensi Pada Pasien Yang Berobat di Klinik Paradise Surabaya Bulan Oktober Tahun 2023 - Salsabila, Elsa; Utami, Sri Lestari; Sahadewa, Sukma (Calvaria Medical Journal, 2024)
One of the current health problems is hypertension, this involves an increase in blood pressure above normal. Blood pressure above 140/90 mmHg indicates that the systolic pressure when the heart pumps blood throughout the body is 140 mmHg and the diastolic pressure when the heart relaxes is 90 mmHg. This research uses a secondary data collection method for patients with hypertension seeking treatment at the Paradise Clinic in Surabaya in 2023, with a total sampling of 49 hypertensive patients. Data were analyzed using bivariate analysis tests, and then chi-square tests. The results of the research on age and hypertension obtained a P-value of 0.008, there was a relationship between the variables tested and based on gender and hypertension, the P-value of 0.075 was greater than 0.05, so there was no relationship. The research conclusion is that there is an influence of age risk factors on hypertension, and there are more men aged under 45 to 55 years than women and gender risk factors have no effect on the incidence of hypertension.